2018
DOI: 10.1037/fam0000457
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of interventions for improving well-being in custodial grandfamilies.

Abstract: Despite the rising cultural phenomenon of grandparents parenting grandchildren on a full-time basis due to problems within the birth parent generation, intervention studies with these families have been scarce, methodologically flawed, and without conceptual underpinnings. We conducted a randomized clinical trial (RCT) with 343 custodial grandmothers recruited from across 4 states to compare the effectiveness of behavioral parent training (BPT), cognitive-behavioral therapy (CBT), and information-only control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…Furthermore, parenting programs have been shown to be useful with parents who have serious mental health problems such as depression and bipolar disorder (Calam & Wittkowski, 2017; Sanders & McFarland, 2000), high levels of couple conflict over parenting and marital breakdown (Stallman & Sanders, 2014), and parents with histories of domestic violence, substance abuse and homelessness (Haskett, Armstrong, Neal, & Aldianto, 2018). Parenting programs can also have a multigenerational benefit, as illustrated by trials of Group Triple P with both custodial and non-custodial grandparents (Kirby & Sanders, 2014; Smith, Hayslip, Hancock, Strieder, & Montoro-Rodriguez, 2018).…”
Section: Parenting Intervention As a Context To Promote Changementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, parenting programs have been shown to be useful with parents who have serious mental health problems such as depression and bipolar disorder (Calam & Wittkowski, 2017; Sanders & McFarland, 2000), high levels of couple conflict over parenting and marital breakdown (Stallman & Sanders, 2014), and parents with histories of domestic violence, substance abuse and homelessness (Haskett, Armstrong, Neal, & Aldianto, 2018). Parenting programs can also have a multigenerational benefit, as illustrated by trials of Group Triple P with both custodial and non-custodial grandparents (Kirby & Sanders, 2014; Smith, Hayslip, Hancock, Strieder, & Montoro-Rodriguez, 2018).…”
Section: Parenting Intervention As a Context To Promote Changementioning
confidence: 99%
“…As adults transition into other stages of life (e.g., becoming a grandparent) they can still benefit from participation in parenting programs (Kirby & Sanders, 2014). Smith et al (2018) in an RCT involving custodial grandparents that compared EBPS (Group Triple P), CBT and care as usual, found that both Triple P and CBT improved the grandparents’ wellbeing and reduced behaviour problems in grandchildren. Furthermore, differences in roles and expectations of grandparents based on cultural differences can create additional sources of both support and conflict.…”
Section: Emerging Issues In Evidence-based Parenting Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interventions to support grandparent caregivers have adopted a stress and coping framework, emphasizing such constructs as resilience or resourcefulness (Choi et al, 2016;Musil et al, 2019) or employing a family-stress model (Smith et al, 2018). A recent meta-analytic review (Chan et al, 2019) concluded that interventions for grandparent caregivers do have positive effects concerning various well-being-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analytic review (Chan et al, 2019) concluded that interventions for grandparent caregivers do have positive effects concerning various well-being-related outcomes. Relying on the family-stress framework, Smith et al (2018) found both parenting skills and cognitive-behavioral programs to be superior to a nonskill-based control (social support) condition in positively impacting grandmothers' well-being and their grandchildren's emotional/behavioral outcomes. The salience of such work is underscored by research suggesting that while grandparents' relationships with grandchildren are associated with positive well-being, this is not the case when they engage in extensive childcare or caregiving responsibilities (Thomas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%